(untitled) (Journal of Medical Sciences, 2023)
A series of hereditary illnesses known as muscular dystrophy result in progressive muscle weakening and wasting. Muscular dystrophy can take many various forms, and the incidence rates vary depending on the type and the demographic being researched. The study’s objective was to determine the prevalence of muscular dystrophy disorders in Libya’s southern area, This study also aims to explain the difficulties and challenges faced by the Scientific Committee and its branches in other southern regions as a first experience with muscular dystrophy patients in terms of sorting and diagnosing these cases. 85 patients had highly suspected hereditary muscular dystrophy, 78 of the 85 patients had positive genetic results.